La salud bucal en el marco de la crisis venezolana - Romero Uzcátegui, Yajaira (2020)
For many Latin American countries, oral diseases have been an unattended issue and rarely seen as a priority in health policies. In the Venezuelan case, the oral health situation has particular characteristics, as a result of the economic crisis that has impacted all areas of social life. The purpose of this scientific note is aimed at analyzing the situation of the oral health component in the Venezuelan population in the framework of the national crisis and the contradictions between the official discourse and the application of public and health policies. Information about what is happening in relation to the operation of dental services in the public and private healthcare network is unknown and it is necessary to develop strategies that allow dental professionals committed to collective health, provide effective responses in order to fulfil the new needs of the population.